Novel pyrazolo[3, 4‐b]pyridine derivatives: Synthesis, structure–activity relationship studies, and regulation of the AMPK/70S6K pathway. Issue 7 (12th April 2022) - Guo, Yating; Jiang, Xiaoding; Chang, Qi; Xiao, Zhihong; Chen, Zhuo; Jiang, Dejian; Hu, Gaoyun; Li, Qianbin
Abstract: A series of novel pyrazolo[3, 4‐ b ]pyridine derivatives were designed, synthesized, and biologically evaluated for anti‐lung cancer activity. Structure–activity relationship and AutoGPA models were constructed based on the in vitro antiproliferative potency of the compounds against a human lung adenocarcinoma cell line (A549). Compound 9d exhibits improved potency for A549 cell growth inhibition (3.06 ± 0.05 μM) compared with A‐769662 (45.29 ± 2.14 μM). Compound 9d can elevate the phosphorylation levels of adenosine monophosphate‐activated protein kinase (AMPK) and its substrate acetyl‐CoA carboxylase and reduce the level of phosphorylated ribosomal S6 kinase (p‐70S6K) at 1 μM, which is comparable to the activity of A‐769662 at 20 μM. 9d induced G2/M cell cycle arrest, which was rescued when co‐incubated with "Compound C, " a potent AMPK inhibitor. Taken together, compound 9d showed potential anti‐lung cancer activity via inducing cell cycle arrest by regulation of the AMPK/70S6K pathway in A549 cells, which could provide a new lead for the discovery of anti‐lung cancer agents. Abstract : Novel pyrazolo[3, 4‐ b ]pyridine derivatives were designed, synthesized, and evaluated for their in vitro anti‐lung cancer activity on A549 cells. Compound 9d showed potential anti‐lung cancer activity via inducing G2/M cell cycle arrest by regulation of the AMPK/70S6K pathway in A549 cells, which could provide a new lead for the discovery of anti‐lung cancer agents.